Development of Student Worksheets based on the Discovery Learning Model on Magnetic Materials in Class VI Elementary School - Nismidawati Nismidawati; Mulyadi Mulyadi; Fatia Fatimah (Postgraduate School, Universitas Negeri Padang, 2022)
This research was motivated by the observations of researchers with the findings of a lack of the student worksheet (LKPD) teaching materials in learning in Elementary School theme 5 Entrepreneurship, the subject matter of Magnets to improve scientific literacy at the elementary level. The purpose of the research is to produce LKPD based on Discovery Learning to improve students' scientific literacy on magnetic material in class VI. The development model chosen in this research is the development of the ADDIE model with the stages of Analysis, Design, Development, Implementation, and Evaluation. The results of the Validation Test stated that the LKPD of the Discovery learning model to improve Science Literacy was very valid to be used at 3.58 or 89.5%. Meanwhile, in the Practicality test, which is seen from the responses of teachers and students, it is stated that practical learning media is used with a percentage of 90.1%. 13 students like learning media or 92.8%. To test the effectiveness of the LKPD it affects the activities and learning outcomes of students before and after use. The use of LKPD also succeeded in increasing students' scientific literacy with 5 indicator competencies referring to PISA from 45.17% to 97.14%. Based on the results of the study, it was concluded that LKPD Discovery Learning can improve students' scientific literacy and is very valid, practical, and effective in the learning process in class VI theme 5 Entrepreneurship.